IMPLEMENTING OF POLYTECHNIC STUDENTS’ ABILITY OF WRITING APPLICATION LETTERS - Masrul Huda; Gozali Gozali (UIN Alauddin Makassar, 2020)
Writing an English application letter is one of ‘Job Getting’ materials. The writing results can measure the students’ writing ability in English. This study aims to describe the writing quality of English application letter made by State Polytechnic of Balikpapan students. It also tries to explain frequent errors in the application letter. The research method used is descriptive qualitative. The data obtained were assessed based on a scoring rubric adapted from Cohen (1994). There are four criteria assessed including Content, Organization, Grammar, and Mechanic. The data results are presented in the tables, graphs, and description. The results show (1) Most of the students' abilities are at Scale 4 and none has the ability at Scale 1. The average number of each component is Content 3,95; Organization 3,89; Grammar 3,38; and Mechanic 3,30. (2) Errors made in writing application letters can be found in all components. Most mistakes were made by students in all components, respectively, mechanic, grammar, organization, and content.